NF-κB inhibitors gifted by nature: The anticancer promise of polyphenol compounds - Chengcheng Guan; Xintong Zhou; Huayao Li; Xiaoran Ma; Jing Zhuang (2022)
Polyphenol compounds are natural antioxidants, which are rich in anti-inflammatory and antioxidant components. They have a wide range of medicinal benefits that are believed to improve human health across various aspects; especially its anticancer effect has been gradually confirmed. The anticancer effect of polyphenols is mainly based on their strong antioxidant and immunomodulatory effects. The innate and adaptive immune responses as well as the development and maintenance of cells and tissues of the immune system are regulated by the NF-κB family of transcription factors. Dysregulation of NF-κB can lead to autoimmune diseases, chronic inflammation, and even cancer. Polyphenol compounds can exert antioxidant and immunomodulatory effects by targeting NF-κB, thus hindering the occurrence and development of tumors.Polyphenol compounds have unique advantages over conventional anticancer therapies such as chemotherapy because they have few side effects and do not cause toxicity to healthy cells. Additionally, they can attenuate the toxic effects of current anticancer therapies. Based on these characteristics, polyphenols have great potential in the prevention and treatment of cancer. This article systematically summarizes the mechanism of NF-κB in tumor genesis, progression, metastasis, angiogenesis, and drug resistance. In addition, we present the anticancer effect of polyphenol compounds by targeting NF-κB during the different stages of tumorigenesis.